2012
DOI: 10.1159/000345864
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Cone Dimensions to Achieve Negative Excision Margins after Large Loop Excision of Transformation Zone in the Uterine Cervix for Cervical Intraepithelial Neoplasia

Abstract: Aims: To determine appropriate cone dimensions for predicting margin status after large loop excision of transformation zone (LLETZ) treatment. Methods: An observational study performed at the Colposcopy Unit of a university hospital setting involving patients who underwent LLETZ conisation within a 1-year period. Data concerning the characteristics, cone dimensions, lesion grade and excision margins of the patients were recorded. Results: The median age of the women (n = 61) was 38 years (18-53). LLETZ cone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 16 publications
4
43
1
Order By: Relevance
“…Papoutsis et al (13) reported that the optimal cut-off value of cone depth to achieve clear surgical margins is 10 mm; however, Kliemann et al (2) showed that the mean depth of cone specimens were 17.1 mm and 22.4 mm among the patients with positive and negative surgical margins, respectively. We found that cone depth was significantly different between margin-positive and margin-negative patients, but multivariate analysis showed that cone depth alone was not an independent predictor of margin status.…”
Section: Discussionmentioning
confidence: 99%
“…Papoutsis et al (13) reported that the optimal cut-off value of cone depth to achieve clear surgical margins is 10 mm; however, Kliemann et al (2) showed that the mean depth of cone specimens were 17.1 mm and 22.4 mm among the patients with positive and negative surgical margins, respectively. We found that cone depth was significantly different between margin-positive and margin-negative patients, but multivariate analysis showed that cone depth alone was not an independent predictor of margin status.…”
Section: Discussionmentioning
confidence: 99%
“…Conization was performed using a diathermal electrocauterizer, which uses high-frequency waves [12]. The pathologic analysis was performed by the pathologists at the same institution.…”
Section: Methodsmentioning
confidence: 99%
“…As to CKC, cervical lesions were removed with a cryoscalpel, the excisional extent and depth can be controlled, and there is no electrocauterization damage to surrounding tissue. It has already been acknowledged that the specimens obtained by LEEP are significantly smaller and contain less of the cervical canal and thus less healthy tissue than cones obtained by CKC [12,13]. …”
Section: Discussionmentioning
confidence: 99%